Fundamentals of international oil and gas law - Hughes, William E., 1944- (PennWell Corporation, 2016)
This book provides a foundation for understanding legal problems commonly encountered in conducting business in the oil and gas industry. Written for a global audience, author devotes substantial attention to industry legal problems arising under non-U.S. legal systems like those in the European Union and Islamic law regimes. Including case studies, and end of chapter questions and notes, this book is an excellent desk reference, course textbook, or introductory guide to this important subject matter.
Keywords: Petroleum industry and trade.; Petroleum law and legislation.; Natural gas -- Law and legislation.; International law.; elektronické knihy; electronic books